Microemulsões: Estrutura e aplicações como sistema de liberação de fármacos - Oliveira, Anselmo Gomes de [UNESP]; Scarpa, Maria Virgínia [UNESP]; Correa, Marcos Antonio [UNESP]; Rodrigues Cera, Luciane Flávia [UNESP]; Formariz, Thalita Pedroni [UNESP] (FapUNIFESP (SciELO), 2004)
Depending on formula composition, microemulsions may be used as a vehicle for drug administration. In this work the main applicable parameters used in the development of pharmaceutical microemulsions (ME) are analyzed. The conceptual description of the system, theoretical parameters related to formation of internal phases and some aspects of ME stability are described. The pseudo ternary phase diagram is used to characterize ME boundaries and to describe different structures in several regions of the diagram. Some applications of ME as drug delivery systems for different administration routes are also analyzed. ME offer advantages as drug delivery systems, because they favor drug absorption, being in most cases faster and more efficient than other methods in delivering the same amount of drug.
Microemulsions: Structure and application as drug delivery systems
Keywords: Drug delivery; Drug incorporation; Microemulsions; drug vehicle; chemical composition; drug absorption; drug delivery system; drug manufacture; drug stability; drug structure; microemulsion